Children's Recidivist who Conducted Criminal Act: Legal Psychology Perspective - Ratnawati, Ratnawati (Faculty of Law, Hasanuddin University, 2020)
Children's social environment influences their psychological return to crimes, and it is a treatment or reward from friends which they consider right since they are encouraged to repeat their actions. The research is an empirical legal research. The results shows that The role of psychologists in Special Child Development Institutions is not optimal, due to limited resources. Furthermore, parents or families should actively supervise and limit the association of children as this will prevent them from returning to the social environment. This is because the environment encourages them to commit criminal acts. Also, the government should make provision for their development through the Ministry of Rights and human rights psychologists of any special institute for children's development.